Susu Formula, Status Pekerjaan STATUS PEKERJAAN IBU DENGAN PEMBERIAN SUSU FORMULA PADA BAYI USIA 0-6 BULAN DI DESA WONOSARI KECAMATAN NGORO- MOJOKERTO - Erfiani Mail (Jurnal Keperawatan Malang, 2017)
Abstract According to the National Socio-Economic Survey(NSES) in 2007-2008. There was a reduction of exclusif breastfeeding, 62.2 percent in 2007 to 56.2 percent in 2008. Majority of mother occupation, youthful age mother, and knowladge about breastfeed that given formula to her baby. This study aims to analyze the association between occupational of mothers with formula feeding. This research designed by cross sectional design. 40 respondents taken by Simple Random Sampling. The independent variable in this research were the mother occupation, while the dependent variable was a formula feeding. This research was conducted in the village of the Wonosari District Ngoro-Mojokerto on May 12 to 17 December 2016. The instrument to that was use is questionnaire, data analyzed by Exact Fisher Test. The results of the study indicate that occupational factors almost entirely respondents who worked at 39 of the respondents (97.5%). According to Exact Fisher Test, there was a correlation parent occupation and formula feeding (?=0.05). This because of mother work have no time to give a breastfeed, so they give formula to her baby. Health workers have to be able give information and how to give exclusive breastfeed although mother was working. Keywords: Baby, Formula, Feeding